2018
DOI: 10.1177/1044207318799644
|View full text |Cite|
|
Sign up to set email alerts
|

Applied Behavior Analysis, Students With Autism, and the Requirement to Provide a Free Appropriate Public Education

Abstract: The prevalence of autism has been steadily rising over the previous decades. When the Autism and Developmental Disabilities Monitoring Network, of the Centers for Disease Control and Prevention, first began tracking the rates in 2004, the prevalence of autism was one in 294 children. By 2002, this rate had risen to one in 151; in 2006, one in 111 children were affected; and in their most recent report in 2012, one in 68 children were estimated to have autism (Christensen et al., 2016). In addition to the press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…For many years, research has been focused mostly on young children, school-age children (Hurlbutt & Chalmers, 2004) or on young adults in their 20s and 30s, so the majority of support systems and intervention programs available focus on early intervention for individuals on the autism spectrum (Neely & Hunter, 2014; Stevenson & Correa, 2018). As a result, a system of electronic sensors network to measure physiological parameters associated with emotional state changes for fostering behavioral therapy of children with ASD was developed (Jȩdrzejewska-Szczerska, Karpienko, & Landowska, 2015; Landowska et al, 2014) and also other solutions supporting children with ASD in the classroom (Fage et al, 2018; Roldán-Álvarez et al, 2016) or during typical routines (Alabbas & Miller, 2019).…”
Section: Challenges For the Future And Possible Implementationsmentioning
confidence: 99%
“…For many years, research has been focused mostly on young children, school-age children (Hurlbutt & Chalmers, 2004) or on young adults in their 20s and 30s, so the majority of support systems and intervention programs available focus on early intervention for individuals on the autism spectrum (Neely & Hunter, 2014; Stevenson & Correa, 2018). As a result, a system of electronic sensors network to measure physiological parameters associated with emotional state changes for fostering behavioral therapy of children with ASD was developed (Jȩdrzejewska-Szczerska, Karpienko, & Landowska, 2015; Landowska et al, 2014) and also other solutions supporting children with ASD in the classroom (Fage et al, 2018; Roldán-Álvarez et al, 2016) or during typical routines (Alabbas & Miller, 2019).…”
Section: Challenges For the Future And Possible Implementationsmentioning
confidence: 99%
“…Litigation related to ASD constitutes a larger portion of court cases in comparison to other special education classifications and even after the prevalence of ASD is accounted for (Zirkel, 2011). Many ASD‐related court cases concern free and appropriate education and the least restrictive environment and involve high‐stakes issues such as the appropriateness of programming and tuition reimbursement (Stevenson & Correa, 2019; Zirkel, 2011). Evaluation and eligibility are sometimes implicated within court cases related to IDEA violations for children with ASD, but not as often as other issues (Fogt et al, 2003).…”
Section: Current Challenges In Identification and Treatment Of Asdmentioning
confidence: 99%
“…Further, although previous court rulings have suggested that students with autism did not have a right to any particular method, including ABA (Stevenson & Correa, 2019), recent due process cases, litigation, and legislation in states such as Louisiana, Hawaii, and Oregon have shined a light on the growing evidence for ABA as the most effective approach for students with ASD (Hart Barnett, Zucker, & More, 2021). And as they become more familiar with federal and state laws and relevant judicial decisions, many more parents will likely pursue legal avenues to advocate for their children’s access to ABA treatments.…”
Section: The Legal Strugglementioning
confidence: 99%
“…Schools have a responsibility under IDEA to provide appropriate services for students all along this spectrum. But as the number of autism diagnoses has increased, many school districts have struggled to educate students with autism who require a high level of support and related services delivered by professionals with specialized expertise (Stevenson & Correa, 2019).…”
mentioning
confidence: 99%